1984
DOI: 10.1111/j.1464-410x.1984.tb07153.x
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin Synthetase Inhibitors and their Effect on Urinary Calcium Excretion and other Parameters in Idiopathic Hypercalciuria

Abstract: The treatment of idiopathic hypercalciuric stone formers with the prostaglandin synthetase inhibitors flurbiprofen and indomethacin has been studied in two phases. Ten patients were studied in a metabolic unit for 14 days that included a control period of 7 days on a controlled intake of dietary calcium, followed by treatment with flurbiprofen 50 mg tds. Three patients were studied along similar lines and were treated with indomethacin 25 mg tds. A significant reduction in urinary calcium excretion was noted d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1985
1985
1997
1997

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Glomerular filtration rates and urine excretion were reduced altogether. If hypercalciuria can be reduced by dietary means, no further decrease of calcium excretion can be attained by prostaglandin synthetase inhibitors [38], Colette et al [13] reported an increase in calcium excretion after indomethacine ad ministration in 7 healthy persons and concluded that the calcium-decreasing effect was only recognizable in idio pathic hypercalciuria patients.…”
Section: Introductionmentioning
confidence: 99%
“…Glomerular filtration rates and urine excretion were reduced altogether. If hypercalciuria can be reduced by dietary means, no further decrease of calcium excretion can be attained by prostaglandin synthetase inhibitors [38], Colette et al [13] reported an increase in calcium excretion after indomethacine ad ministration in 7 healthy persons and concluded that the calcium-decreasing effect was only recognizable in idio pathic hypercalciuria patients.…”
Section: Introductionmentioning
confidence: 99%